Use of reciprocating electromagnetic vibration motor equipment for the separation of grape seeds from marc - Gela Javakhishvili (Scientific Research and Experimental Development, 2024)
The most important place in the grape oil production chain is the separation of grape seeds from marc. Most separation machines are equipped with rotary engines. The productivity of such a car depends significantly on the physical and mechanical condition of the marc. In such machines, the engine rotation frequency can be adjusted with a frequency regulator or a reducer, which in turn increases the cost and complicates the operation process. We offer a machine for separating grape seeds from marc, equipped with a reciprocating electromagnetic vibrating motor, which can be driven by our patented reсiprocating electromagnetic vibrating motors with direct current (DC) biasing, where it is possible to adjust the vibration of the working body by the use of bias current change.